Women in Kentucky - Irvin, Helen D. (Book collections on Project MUSE., 2015)
In more than two hundred years of statehood, most Kentucky women have been invisible to history. Yet from the first settlement, women have been prominent contributors to Kentucky history and culture. Women in Kentucky tells the stories of the ordinary women of lonely frontier farms, the women both black and white whose lives were shaped by slavery, and the laboring women of the factories and shops in rising urban centers. Helen Deiss Irvin also profiles the exceptional Kentucky women whose lives became more visible: abolitionist Delia Webster, suffragists Laura Clay and Madeline McDowell Brec.